Предмет:
МатематикаАвтор:
rosebudvbso1)
8 - 18 = 8 + (-18) = -10
8 - (-18) = 8 + (-(-18)) = 8 + 18 = 26
-8 - 18 = -8 + (-18) = -26
- 8 - (-18) = -8 + (-(-18)) = - 8 + 18 = 10
2)
13 - 9 = 13 + (-9) = 4
13 - (-9) = 13 + (-(-9)) = 13 + 9 = 22
-13 - 9 = -13 + (-9) = -22
-13 - (-9) = -13 + (-(-9)) = -13 + 9 = -4
Автор:
highbeamlnmjДобавить свой ответ
Предмет:
МатематикаАвтор:
jaylinallisonОтветов:
Смотреть
Предмет:
МатематикаАвтор:
damariduarteОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
callieuib6Ответов:
Смотреть
Предмет:
ФизикаАвтор:
harrymaxwellОтветов:
Смотреть